Interferensi Sintaksis Bahasa Indonesia terhadap bahasa Jerman pada Schriftlicher Ausdruck dalam Matakuliah B1-Prüfüngsvorbereitung - Kirana Anjastya Prima Raymondra; Herri Akhmad Bukhori (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: Interference is a language error in the mixing of first language elements into the second language. One of the error types is composing a second language sentence using the structure of the first language. This phenomenon is discussed in syntax. Syntax is the linguistic branch that refers to the rules for arranging words and phrases to make a well-formed sentence. The purpose of this study is to identify Indonesian syntactic interference toward German on the texts Schriftlicher Ausdruck taken from the B1-Prüfungsvorbereitung-course. The total number of texts was 21. Sentences containing Indonesian syntactic interference were recorded in the documentation table and analyzed using the language error theory by James and Corder. The results showed that there are one hundred and ten-sentence data containing Indonesian syntactic interference. The data are grouped into error and mistake categories. The data that include errors are interference of word order in a sentence, omission of sentence elements (subject, reflexive pronoun, verbs, conjunction), the addition of sentence elements (preposition), and use of sentence element (conjugation). The data that include mistakes are interference of the use of sentence elements (verb according to the context of the sentence, conjunction, preposition, adverb, and word). Keywords: interference, syntax, schriftlicher ausdruck Abstrak: Interferensi adalah kesalahan berbahasa berupa bercampurnya unsur bahasa pertama ke dalam bahasa kedua. Salah satu kesalahan tersebut seperti menulis kalimat bahasa kedua menggunakan aturan pembentukan kalimat bahasa pertama. Fenomena ini dibahas dalam sintaksis. Sintaksis merupakan cabang linguistik yang khusus membahas aturan penyusunan kata dan frasa untuk membentuk kalimat dengan susunan yang tepat. Penelitian ini bertujuan mengidentifikasi interferensi sintaksis bahasa Indonesia terhadap bahasa Jerman pada teks karangan schriftlicher Ausdruck yang diambil dari mata kuliah B1-Prüfungsvorbereitung. Keseluruhan karangan yang diteliti berjumlah 21. Kalimat yang mengandung interferensi sintaksis bahasa Indonesia di data pada tabel dokumentasi dan dianalisis menggunakan teori kesalahan berbahasa oleh James dan Corder. Hasil penelitian menunjukkan terdapat seratus sepuluh data kalimat yang mengandung interferensi sintaksis bahasa Indonesia. Data tersebut dikelompokkan ke dalam error dan mistake. Data yang termasuk error yaitu interferensi urutan kata dalam kalimat, penanggalan unsur kalimat (subjek, pronomina refleksif, verba, konjungsi), penambahan unsur kalimat (preposisi), dan penggunaan unsur kalimat (konjungsi). Data yang termasuk mistake adalah interferensi penggunaan unsur kalimat (verba sesuai konteks kalimat, konjungsi, preposisi, adverbia, dan kata). Kata kunci: interferensi, sintaksis, schriftlicher ausdruck